The Roles of Public Relations as A Facilitator of Communication in Handling Complaints at PLN East Java Distribution - Muchamad Rizqi; Mohammad Insan Romadhan; Devi Kurnia Inayati (2020)
In PLN East Java Distribution, it is known that the role of Public Relations is a major key in solving the problem of a company or organization given that the PLN East Java Distribution is the provider of electricity for corporate, residential, hotel, and others. This study has the objective to analyze the roles of Public Relations of PLN East Java Distribution in handling customer complaints, by using Public Relations model approach namely two-way asymmetric. This study used a qualitative research method with descriptive approaches: case study, interviews, observation and documentation. Data analysis using Interactive analysis models called Miles and Huberman. The results in this study Public Relations PLN East JavaDistribution bridging communications with customers using multiple media such as printed media, social media, and electronic media in response to customer complaints